2002
DOI: 10.1046/j.1365-4362.2002.01391.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two surgical approaches for treating vitiligo: a preliminary study

Abstract: The thin split-thickness graft technique is superior to the suction blister technique in treating vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…Blister roof grafts vs. split-thickness skin grafts. Ozdemir et al 24 compared these two techniques. Twenty patients were included in this study.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…Blister roof grafts vs. split-thickness skin grafts. Ozdemir et al 24 compared these two techniques. Twenty patients were included in this study.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…Compared to the suction blister grafting ultra thin epidermal skin grafting can cover a larger surface area. Ozdemir et al, (9) demonstrated a higher percent of repigmentation with this ulta thin (10) as compared to mini punch grafting this technique produces far more cosmetically superior results and matching over larger areas. In our opinion, the ultrathin skin graft technique is found to be simple, economical, less time consuming with good cosmetic appearence.…”
Section: Discussionmentioning
confidence: 90%
“…(29)(30)(31) The repigmentation rate in these studies according to the review by Njoo et al was 87%, whereas Ozdemi et al reported rates between 25% -65%. (29)(30)(31)(32)(33)(34)(35)(36) In the study by Maleki et al, ten patients with refractory vitiligo who were treated by suction blister graft and subsequent PUVA therapy reported over 90% repigmentation in seven patients. In studies of blister grafting followed without phototherapy, i.e.…”
Section: Discussionmentioning
confidence: 99%